Pentalogy of Cantrell in Full Term Neonate - Nadereh Taee; Mojgan Faraji Goodarzi; Mohammad Safdari; Amir Bajelan (Thieme Medical Publishers, Inc., 2019)
Pentalogy of Cantrell (PC) is an uncommon congenital disorder characterized by severe defects in the chest and abdomen, including abdominal visceral prolapsed via umbilical cord (omphalocele), defect in the lower part of the sternum, defect in the front of the diaphragm, defects in the anterior part of the pericardium, and the ectopiacordis. Here, we report a 2-hour-old girl, weighing 3,500 g, who was referred to Shahid Madani Hospital in Khorramabad due to the large omphalocele on her chest with pulsating mass above it. The baby was the first child of a 24-year-old mother who was born with an uncomplicated vaginal delivery. Very rare cases of PC are born as a term new-born.